2020
DOI: 10.1002/jcla.23406
|View full text |Cite
|
Sign up to set email alerts
|

PRKAA1 rs13361707 C/T polymorphism confers decreased susceptibility to esophageal cancer: A case‐control study

Abstract: Background Several studies probed into the connection between esophageal cancer (EC) risk and PRKAA1 rs13361707 C/T polymorphism, but obtained insignificant findings. Methods In this study, 814 EC cases and 961 controls from Eastern China were recruited to validate the relationship between this polymorphism and EC susceptibility. Results Data suggested rs13361707 C/T polymorphism in PRKAA1 gene was significantly related with a lower risk for EC. Such significant connection was also uncovered in subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…We analyzed the PRKAA1 polymorphic loci rs13361707, rs3792822, and rs10074991. In our study, the variation frequency of rs13361707 in healthy subjects was 72.88%, which was similar to the 71.8% reported by previous research ( Li et al, 2020 ). Otherwise, it was different from the 80.86% reported by Yuan et al (2016) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We analyzed the PRKAA1 polymorphic loci rs13361707, rs3792822, and rs10074991. In our study, the variation frequency of rs13361707 in healthy subjects was 72.88%, which was similar to the 71.8% reported by previous research ( Li et al, 2020 ). Otherwise, it was different from the 80.86% reported by Yuan et al (2016) .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found that gene polymorphisms are closely related to drug metabolism and disease occurrence ( Wang et al, 2013 ; Mei et al, 2015 ; Guo et al, 2021 ). However, there are few studies on the correlation between AMPK gene polymorphisms and gastric cancer, rectal cancer, diabetes mellitus and Hepatitis B virus infection ( Lee et al, 2014 ; Yuan et al, 2016 ; Chen et al, 2018 ; Jiang et al, 2018 ; Li et al, 2020 ). Our previous study identified that the PRKAA2 gene polymorphism had a significant effect on PHN susceptibility ( Mei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%